Creating a National Provider Identifier (NPI) to Unique Physician Identification Number (UPIN) Crosswalk for Medicare Data. Issue 12 (December 2017) - Parsons, Helen M.; Enewold, Lindsey R.; Banks, Robert; Barrett, Michael J.; Warren, Joan L.
Abstract : Introduction: Many health services researchers are interested in assessing long term, individual physician treatment patterns, particularly for cancer care. In 2007, Medicare changed the physician identifier used on billed services from the Unique Physician Identification Number (UPIN) to the National Provider Identifier (NPI), precluding the ability to use Medicare claims data to evaluate individual physician treatment patterns across this transition period. Methods: Using the 2007–2008 carrier (physician) claims from the linked Surveillance, Epidemiology and End Results (SEER) cancer registry-Medicare data and Medicare's NPI and UPIN Directories, we created a crosswalk that paired physician NPIs included in SEER-Medicare data with UPINs. We evaluated the ability to identify an NPI-UPIN match by physician sex and specialty. Results: We identified 470, 313 unique NPIs in the 2007–2008 SEER-Medicare carrier claims and found a UPIN match for 90.1% of these NPIs (n=423, 842) based on 3 approaches: (1) NPI and UPIN coreported on the SEER-Medicare claims; (2) UPINs reported on the NPI Directory; or (3) a name match between the NPI and UPIN Directories. A total of 46.6% (n=219, 315) of NPIs matched to the same UPIN across all 3 approaches, 34.1% (n=160, 277) agreed across 2 approaches, and 9.4% (n=44, 250) had a match identified by 1 approach only. NPIs were paired to UPINs less frequently for women and primary care physicians compared with other specialists. Discussion: National Cancer Institute has created a crosswalk resource available to researchers that links NPIs and UPINs based on the SEER-Medicare data. In addition, the documented process could be used to create other NPI-UPIN crosswalks using data beyond SEER-Medicare.